Complex behavioral plasticity is not reduced in spiderlings with miniature brains - Quesada Hidalgo, Rosannette (2021)
The brains of smaller animals are smaller than those of their larger relatives, but it is not clear whether their adaptive behavioral flexibility is more limited. Previous interspecific comparisons found that aspects of web construction behavior of very small orb weaving spiders (0.005 mg) were no less precise than those of much larger related orb weavers (30 mg), but the behaviors tested were relatively simple. Here we perform a more sensitive intraspecific test involving the multiple behavioral adjustments of orb web designs made by Leucauge argyra to confinement in very small spaces. Web adjustments of spiderlings as small as ~0.1 mg were compared to previously published observations of ~80 mg conspecific adults. Spiderlings in constrained spaces made all of the complex adjustments made by adults in at least seven independent web design variables, and their adjustments were no less precise. Rough estimates based on previously published data on total brain volumes and the mean diameters of neuron cell bodies suggested that spiderlings and adult females of Leucauge may have similar numbers of neurons, due to spiderlings having smaller neurons and a greater percentage of body tissues dedicated to the brain. We speculate that this neural similarity may explain why L. argyra spiderlings showed no behavioral deficits compared with adults.